Measuring research in the university via senior academic promotions and faculty research metrics - Brennan, Niamh; Kiely, Kevin (My University, 2019)
CRIS systems are well suited for measuring research activity in a university. There are several reasons for measuring research activity from various perspectives: national, university, school, department, research institution, strategic theme, as well as at the individual level. The CRIS system’s position as an enterprise system with interfaces to other enterprise systems such as the HR system facilitates this multifaceted approach. This paper describes two recent initiatives based on the Research Support System (RSS) CRIS in Trinity College Dublin. The Senior Academic Promotions call allows academics to apply for promotion to the grades of Professor and Associate Professor. Faculty Research Metrics is the latest iteration of the university’s research quality metrics, which allows for each of the three faculties to define their own sets of research quality metrics.
PUBLISHED
Keywords: CRIS; Promotions; HR; metrics; university; research evaluation; academic rewards; Digital Engagement